2000
DOI: 10.1002/1521-3757(20001117)112:22<4200::aid-ange4200>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Das „Wanzlick-Gleichgewicht“

Abstract: 1,3‐dialkylierte Benzimidazolin‐2‐ylidene sind der Schlüssel für den Nachweis des so genannten Wanzlick‐Gleichgewichts zwischen elektronenreichen Tetraaminoethylenen und N‐heterocyclischen Carbenen [Gl. (1)]. Dieses Gleichgewicht wurde kürzlich von zwei Arbeitsgruppen unabhängig von einander nachgewiesen. Ausgehend von Dibenzotetraazafulvalenen wurde es in Abwesenheit von Elektrophilen NMR‐spektroskopisch quantifiziert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Wanzlick Equilibrium [32] In his early papers, [33][34][35] Wanzlick proposed that tetraaminoethenes dissociated reversibly to generate diaminocarbenes to account for the reaction of the former with electrophiles to give products apparently derived from the carbene (his examples were all dihydroimidazol-2-ylidenes). However in 1964 Lemal et al [36] showed that typical tetraaminoethenes did not dissociate, even under much more drastic conditions than used by Wanzlick et al, by carrying out a negative crossover experiment (Scheme 2 a, Ar = p-tolyl).…”
Section: The Controversy Concerning the Kinetics Of Thementioning
confidence: 99%
“…Wanzlick Equilibrium [32] In his early papers, [33][34][35] Wanzlick proposed that tetraaminoethenes dissociated reversibly to generate diaminocarbenes to account for the reaction of the former with electrophiles to give products apparently derived from the carbene (his examples were all dihydroimidazol-2-ylidenes). However in 1964 Lemal et al [36] showed that typical tetraaminoethenes did not dissociate, even under much more drastic conditions than used by Wanzlick et al, by carrying out a negative crossover experiment (Scheme 2 a, Ar = p-tolyl).…”
Section: The Controversy Concerning the Kinetics Of Thementioning
confidence: 99%
“…NMR experiments revealed decomposition of [(NHC)(PPh 3 )PdI 2 )] to [(NHC) 2 PdI 2 )] and trans [Pd(PPh 3 ) 2 I 2 ] over the course of several days (Scheme 1). [16] In contrast to this result, the reaction of [NiX 2 (PPR 3 ) 2 ] (X=Cl, Br) with NHCs showed the substitution of the sterically demanding phosphine ligands by carbene ligands [17,18] …”
Section: Introductionmentioning
confidence: 96%
“…[16] In contrast to this result, the reaction of [NiX 2 (PPR 3 ) 2 ] (X=Cl, Br) with NHCs showed the substitution of the sterically demanding phosphine ligands by carbene ligands. [17,18] We have recently reported the synthesis of 1-(n-butyl)-3-N-(2-Ar)acetamido-1, 3-imidazolium chloride (Ar = furylmethyl,phenylmethyl) and their reactivity towards [NiCl 2 (PÀ P)] (LÀ L=2 PPh 3 , dppf). [5] The interesting outcomes of our previous study prompted us to further explore the chemistry of these imidazolium salts towards palladium metal precursors and study their promising catalytic activities for Suzuki coupling reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Nevertheless, NHC molecules are known to dimerize in solution, [5] thereby reducing the effectiveness of the ligand (in its monomeric form) to coordinate with metal centers. Dimerization of NHCs, first proposed by Wanzlick, [6] has been a subject of interest both experimentally and theoretically. [7] A direct approach mechanism of NHC monomers to form a dimer, though highly exothermic, has been found to have prohibitively large activation energy.…”
mentioning
confidence: 99%